THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY(CSR) AND CUSTOMER-BASED BRAND PREFERENCE ON PERCEIVED BRAND QUALITY CASE STUDY ON CUSTOMERS CCTV - Chairul Hakim; Disman MS (AIBPM Publisher, 2018)
The purpose of this research is to design CSR and Custumer-Based brand preference on Perceived Brand Quality. The total sample is 54 respondents, which used to the test of hypothesiswas proposed using Structural Equation Model (SEM) analysis.The results of this research showed that CSR has an effect on brand preference but CSR has no effect on Brand Quality Perception, While brand preference influences to Brand Quality Perception.The weakness of this research is the samples are not sufficient. so that the results of research can not be generalized to the wider population. Keyword : CSR, Preferensimerek, Persepsi Brand Quality